The Increasing Cost of Buying American - Matilde Bombardini; Andres Gonzalez-Lira; Bingjing Li; Chiara Motta (CESifo GmbH, 2024)
The latest resurgence in the U.S. of policies aimed at reducing imports and bolstering domestic production has included the expansion of Buy American provisions. While some of these are new and untested, in this paper we evaluate long-standing procurement limitations on the purchase of foreign products by the U.S. Federal Government. We use procurement micro-data to first map and detect employment effects of government purchases and then calibrate a quantitative trade model adapted to include features relevant to Buy American: a government sector, policy barriers in final and intermediate goods, labor force participation, and external economies of scale. We show that, while current Buy American provisions on final goods purchase have created up to 100,000 jobs at a cost of between 111,500 and 137,700 per job, the recently announced tightening of the policy on the use of foreign inputs will create fewer jobs at a higher cost of 154,000 to 237,800 per job. We also find scant evidence of the use of Buy American rules as an effective industrial policy.
Keywords: F10; F13; H41; H57; 330; Buy American; public procurement; trade restrictions; domestic content; Öffentlicher Auftrag; Protektionismus; Wirkungsanalyse; USA